The moral law versus the culture of sin - Constantin, Andrei; Petrov, George Daniel (Technium Social Sciences Journal, 2023)
Sins touch human dignity. There is an undeniable connection between sin and human dignity. We were created for virtue, and sin robs us of the honor of people created in God's image. The fight against sin is a permanent part of the Christian life and it extends throughout our life. But sins bring damage not only to the perpetrator, but also on a social level. Sin takes away human's freedom, bringing him slavery. Sin thus ends up ruining the order of human life, inverting values, overturning them.